EVALUASI SIFAT FISIK NATA DE COCO DENGAN EKSTRAK KECAMBAH SEBAGAI SUMBER NITROGEN - Priyantini Widiyaningrum; Dewi Mustikaningtyas; Bambang Priyono (Universitas Muhammadiyah Semarang, 2017)
Ammonium sulfate (ZA) has a role as nitrogen sources for the growth of bacteria acetobacter xylinum in making nata de coco. In fact, ZA food grade isexpensive and rarely sold in the market. One of the potential ZA substitutes ismungbean sprout extract. This study aimed to compare the physically characterof nata which was processed using two different nitrogen sources, namelymungbean sprout extract and ammonium sulfate (ZA) food grade. This researchwas conducted by simple experimental using one-way classification design. Theraw materials were coconut water, acetic acid, sugar and Acetobacter xylinum,as well as mungbean sprout and ZA food grade as treatment. Nata is harvestedafter 10 days incubation. Physical characteristics is measured includethickness, wet weight, yield, moisture content and fiber content. The result of theobservation was analyzed using unpaired two sample test of Student's t-test. Theresults showed no differences in average thickness, yield, wet weight, moisturecontent, and fiber content in both groups of nata products (t test α> 5%).Utilization of 1% mungbean sprout extract can replacing 0.25% ZA foodgrade in this study. In conclusion, the physically character of nata withmungbean sprout is not different than ZA food grade.Keywords : mungbean sprout, nata de coco, , ZA food grade, physicalanalysis